Potential harmful health effects of inhaling nicotine-free shisha-pen vapor: a chemical risk assessment of the main components propylene glycol and glycerol. Issue 1 (December 2015) - Kienhuis, Anne; Soeteman-Hernandez, Lya; Bos, Peter; Cremers, Hans; Klerx, Walther; Talhout, Reinskje
Abstract Background A shisha-pen is an electronic cigarette variant that is advertised to mimic the taste of a water pipe, or shisha. The aim of this study was to assess the potential harmful health effects caused by inhaling the vapor of a nicotine-free shisha-pen. Methods Gas chromatography analysis was performed to determine the major components in shisha-pen vapor. Risk assessment was performed using puff volumes of e-cigarettes and "normal" cigarettes and a 1-puff scenario (one-time exposure). The concentrations that reached the airways and lungs after using a shisha-pen were calculated and compared to data from published toxicity studies. Results The main components in shisha-pen vapor are propylene glycol and glycerol (54%/46%). One puff (50 to 70 mL) results in exposure of propylene glycol and glycerol of 430 to 603 mg/m3 and 348 to 495 mg/m3, respectively. These exposure concentrations were higher than the points of departure for airway irritation based on a human study (propylene glycol, mean concentration of 309 mg/m3 ) and a rat study (glycerol, no-observed adverse effect level of 165 mg/m3 ). Conclusions Already after one puff of the shisha-pen, the concentrations of propylene glycol and glycerol are sufficiently high to potentially cause irritation of the airways. New products such as the shisha-pen should be detected and risks should be assessed to inform regulatory actions aimed at limiting potential harm that may be caused to consumers and protecting young people to take up smoking.